Interwencyjne wykorzystanie zeolitów w oczyszczaniu ścieków = Emergency use of zeolites in wastewater treatment - Wiśniowska, Ewa; Karwowska, Beata; Sperczyńska, Elżbieta (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper presents the results of the studies on use of selected zeolites in emergency situations in wastewater treatment plants. They were used for removal of ammonium nitrogen from mixtures of wastewater, reject waters and condensates from high-tempearure sludge drying. Zeolite and bentonite at dose of 2g/dm3 were used. The use of zeolites allowed to increase the efficiency of ammonium nitrogen removal about 50% compared to control system.
Keywords: zeolity; azot amonowy; oczyszczanie ścieków; ciecze osadowe; skropliny z suszenia osadów; zeolites; ammonium nitrogen; wastewater treatment; reject waters; condentsates from sewage sludge drying